Efficacy of the context, input, process, and product (CIPP) model in evaluating an EFL curriculum: A review - Younus, Muhammad; Abdullah Adnan, Mohamed; Fatimah, Ali; Mohd Rashid, Ab Hamid (Penerbit UMPSA, 2025)
This review aims to investigate the effectiveness of the CIPP evaluation model and provide insights into its strengths, limitations, and overall efficacy in evaluating an English as a foreign (EFL) curriculum. Three research questions were formulated to investigate how the CIPP model (1) assesses curriculum appropriateness, (2) addresses challenges in EFL instruction, and (3) provides insights into curriculum effectiveness. The research methodology involved collecting papers published over the past five years from reputable databases. Ten articles were thoroughly reviewed, focusing on abstracts, findings, and conclusions. Content analysis was employed to examine research findings on the effectiveness of the CIPP model. The findings reveal the efficacy of the CIPP model in assessing EFL curriculum appropriateness, addressing challenges in EFL instruction, and enhancing EFL programme outcomes. The model demonstrates effectiveness in identifying inadequacies, providing solutions for optimal teaching–learning processes, and facilitating informed decision-making for continuous improvement in language education. In conclusion, the CIPP model emerges as a versatile and effective tool for evaluating EFL programmes, supporting informed decision-making, and contributing to ongoing advancements in language education.